Swarm-based optimization of final arrival segments considering the unmanned aircraft system integration into the non-segregated airspace. - Pinto Neto, Euclides Carlos (2018)
In the past few years, there has been a growth in Unmanned Aircraft Systems (UAS) numbers in segregated airspace. However, although there is an interest in integrating large UAS into non-segregated airspace, the safety challenges on its integration arise from the inclusion of new ways of reaching unsafe states into the airspace. Furthermore, Air Traffic Controllers (ATCo) aim to o?er appropriate levels of safety and efficiency and to solve issues present in complex situations. Although the UAS technology may be used in di?erent situations and brings several advantages to the airspace (e.g. efficiency), it may bring uncertainties due to the fact that ATCos may not be familiar with them. Throughout the years, this impact may be lower then it is nowadays due to the fact that the present lack of familiarity in the relationship between UAS and ATCo contributes to higher workload levels. Furthermore, Terminal Maneuvering Area (TMA), which composes the controlled airspace and in which the final sector in contained, is a critical control area normally established at the confluence of Air Traffic Service (ATS) routes in which the aircraft tend to be closer to each other. Thus, operations in this particular area are conducted carefully and, in order to achieve desirable levels of safety and efficiency, standard procedures are established. In some cases, however, standard procedures cannot be followed and the sequencing of the aircraft during the approach, which is a highly challenging task due to complex maneuvers constraints, must be performed by the ATCo in a manner to respect the minimum separation of aircraft and to avoid flights through cumulonimbus (CB). Finally, the main goal of defining a final arrival segment is to deliver the set of aircraft from the final sector of the TMA to the final phase of its landing procedure, i.e., the final approach, considering the operation efficiency and safety. The main objective of this research is to propose a parallel swarm-based method for optimizing final aircraft arrival segments design, i.e., routes that connects the final sector to the Initial Approach Fix (IAF), considering the UAS presence. This is conducted from two perspectives: ATCo workload, which is related to safety, and sequencing duration, which is related to efficiency. Furthermore, di?erent phases of UAS integration are considered, i.e., from early stages of its integration to a mature stage of its operation by means of the Technology Maturity Level (TML) usage, which is a scale that measure the familiarity between the ATCo with the aircraft. Finally, the solutions consider airspace restrictions such as minimum separation between aircraft and bad weather conditions, i.e., the presence of cumulonimbus (CB). The experiments conducted show that this approach is able to build safe and efficient solution even in situations with a high number of aircraft.